Removal of Physical Properties in Water Supply by WASRA for Sustainable Irrigation System - Abdul Syukor, Abd Razak; Nur Azzimah, Zamri; Norbaizurah, Rahman; Suryati, Sulaiman; Nurhidayah, Mahazam; Hasmanie, Abdul Halim; Edriyana, Abd Aziz (AENSI, 2015)
In irrigation, water is essential to assist in the growing of agricultural crops, maintenance of landscapes, and revegetation of disturbed soils in dry areas and during periods of inadequate rainfall. Most importantly, water quality can be a limiting factor in plant growth. Thus, this study was performed to analyze and compare between raw and treated water by WASRA system in terms of water quality effectiveness. This research also determines the potential groundwater resources for irrigation purposes at University Malaysia Pahang (UMP) nursery based on Interim National Water Quality Standard for Malaysia (INWQS). WASRA system manages to effectively remove 100% suspended solid followed by turbidity 93.59% and colour 89.54%. From the result, it can be concluded that treated groundwater using WASRA system can be used for irrigation purpose at UMP nursery as it can improve the water quality parameter.